PENGGUNAAN EKSTRAK DAUN TREMBESI (Samanea saman (Jacq.) Merr) SEBAGAI INHIBITOR ORGANIK UNTUK MEREDUKSI LAJU KOROSI LOGAM BAJA KARBON - Sarno Setiawan; Yusuf Nasrulloh (Universitas Islam Indonesia, 2020)
Extract of trembesi leafs consist tannins compound that can reducing corrosion rate. This studey was to examine the efficiency of trembesi leaf extract as a inhibitors of corrosion rate. In this study, carbon steel metal was used as an immersion object in 10% HCl solution as a corrosion medium. Trembesi leaf extract were added in the corrosive medium with variations in volumes of 3, 6, 9, 12 mL with carbon steel immersion for 14 days. Corrosion rate was calculated using the weight loss method. The results shows, the lowest corrosion rate was obtained in the addition of 9 mL inhibitor concentration of 0.008989 cm/year and the highest corrosion rate was without the addition of an inhibitor of 0.011669 cm/year. The highest inhibitor efficiency value was 22.97% with the addition of 9 mL.